Government performance and dissatisfaction with democracy in Australia. Issue 2 (2nd April 2020) - Cameron, Sarah
ABSTRACT: Satisfaction with democracy has declined rapidly in Australia, reaching the lowest level recorded since the 1970s in 2019. Whereas Australian citizens used to be among the most satisfied democrats in the world, there is now evidence of widespread dissatisfaction. What explains this rapid decline in political support? Comparative studies emphasise the role of government performance, both political and economic, in shaping citizens' attitudes towards the political system. This paper examines the role of government performance in shaping satisfaction with democracy in Australia, using Australian Election Study data from 1996 to 2019. The results demonstrate that frequent changes of prime minister, which a majority of voters disapproved of, and rising economic pessimism contributed to the decline of democratic satisfaction in Australia.